The Mural Form of Eosinophilic Esophagitis Is Accompanied by Superficial Esophageal Squamous Cell Carcinoma - Zhao Jingsheng; Luo Yuncheng; Miao Yingye; Li Hao; Li Congyang (Case Reports in Pathology)
Eosinophilic esophagitis (EE) is an increasingly recognized primary clinicopathologic disorder of the esophagus which lacks a specific etiology. Most reports on EE have been limited to the esophagus mucosa. We present a 56-year-old man with the mural form of EE and superficial squamous cell carcinoma in the esophagus. The eosinophils diffusely invaded the full-thickness of the esophagus, mainly infiltrating the muscularis, including the skeletal and smooth muscles. The lesions in the mucosa, submucosa, and adventitia were slight. Although the superficial squamous cell carcinoma was excited by an endoscopic biopsy, there were some changes in the architecture and size of the squamous epithelial cells. The changed cells also expressed the p53 protein. It appears that the eosinophils stimulated cell proliferation, followed by genetic mutations and cancer development. The patient survived with resection of the esophagus and inhaled corticosteroids.